Augmented Reality Application for Teaching the History of the Petilasan Damarwulan Cultural Heritage Site - Moh. Anshori Aris Widya; Azmi Zamzami Riyadin (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
This study aims to develop a historical learning media application utilizing augmented reality technology to introduce the cultural heritage site of Petilasan Damarwulan. The research addresses the declining reading interest among younger generations and the lack of interactive media in preserving local culture. A research and development (R&D) approach was employed, following ten stages from needs analysis to product evaluation. The application was built as a web-based platform to ensure compatibility with mobile devices, offering features such as image scanning, three-dimensional visualization, and narrative descriptions of the cultural site. Implementation results indicate that the application enhances users’ understanding of local history and culture. Functional testing using the black-box method confirmed that all features operated as intended. In conclusion, the application proves to be an effective tool for interactive learning and holds potential as a means of supporting digital cultural preservation within primary education environments. Augmented Reality